KORELASI ANTARA RESISTENSI ANTIMIKROBA DENGAN KEMAMPUAN MEMBENTUK BIOFILM PADA ISOLAT PSEUDOMONAS AERUGINOSA DARI SAMPEL SPUTUM ETT DI RUANG RAWAT INTENSIF RSUD DR. SAIFUL ANWAR - Etty Fitria Ruliatna; Lydia Trisnawati; Yuyun Kusumaningrum (RSUD Dr. Saiful Anwar Province of East Java, 2026)
Background: Pseudomonas aeruginosa is a prominent pathogen responsible for hospital-acquired infections. Its pathogenic potential is primarily driven by antimicrobial resistance and the ability to form biofilms. Aim: To examine the correlation between antimicrobial resistance patterns and the biofilm-forming ability of Pseudomonas aeruginosa isolated from endotracheal tube (ETT) sputum specimens. Methods: This analytic cross-sectional study used sputum samples from ICU patients with ETT. Biofilm detection was done using the microtiter plate method, and antimicrobial susceptibility was tested using Vitek. Results: Of the 23 multidrug-resistant (MDR) isolates identified, 45.5% demonstrated biofilm-forming ability, while 54.5% did not. Statistical analysis using the Chi-square test revealed no significant association between antimicrobial resistance and biofilm formation. Conclusion: There was no significant correlation between multidrug resistance and biofilm production in Pseudomonas aeruginosa isolates from ETT sputum samples.